Історія дослідження формування у майбутніх фахівців з харчових технологій англомовних рецептивних комунікативних компетентностей - Ковальчук, Ольга Сергіївна (My University, 2016)
У статті здійснено історико-педагогічний аналіз формування у майбутніх фахівців з харчових технологій англомовних рецептивних комунікативних компетентностей. Узагальнено досвід науковців, що розробляли методику навчання рецептивних видів мовленнєвої діяльності студентів немовних вищих навчальних закладів. Здійснено аналіз розвідок, присвячених формуванню англомовних рецептивних комунікативних компетентностей у студентів технологічних ВНЗ. Зроблено висновок про необхідність ранньої професіоналізації студента, що посилює актуальність англійської мови для професійного спілкування. The field known as English for Specific Purposes through years has now expanded to include over twenty areas. It should, however, be observed the lack of research devoted to the study of teaching English for Food Science. Purpose. The paper is aimed at analyzing current research devoted to developing English receptive communicative competence of students majoring in Food Technology as well as non-linguistic specialties. Results. The review of scientific papers on developing receptive communicative competence at non-linguistic universities demonstrate the significant achievements in the improvement of methods of teaching English for Specific Purposes. The article analyses research by scientists who created methods for developing communicative competence, in particular, receptive communicative competence of students majoring in non-linguistic sciences. Conclusions. The works by most scientists consider a principle of interconnected learning. However, teaching reading and listening occurs by integrating with other types of speech activity, mainly productive ones.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; харчові технології; англійська мова; language skills; english; мовні компетенції; food technology